KEEFEKTIFAN KALIMAT DALAM LAPORAN PERJALANAN SISWA KELAS VIII MTs HIDAYATUL MUSLIHIN 2011/2012 - Sekar Wulandari; Kahfie Nazaruddin; Eka Sofia Agustina (FKIP Universitas Lampung, 2013)
The problem in this research is the efectiveness of sentences in the trip report at the second grade students of MTs Hidayatul Muslihin Way Kanan on academic year 2011/2012. This research aimed to describe the effectiveness of sentences including integrity, alignment, explicity, and frugality in trip report of second grade students of MTs Hidayatul Muslihin Way Kanan on academic year 2011/2012.The method used is descriptive qualitative. The data source for this research is trip report of second grade students of MTs Hidayatul Muslihin Way Kanan on academic year 2011/2012 which consist of 30. From the data source, it has been settled that there are 515 sentences. Based on the result analysis, it was known that effective sentences are 345 sentences with percentage 66,99 , meanwhile ineffective sentences are 170 sentences with percentage 33,01. Ineffective sentences itself consist of unfrugality, unintegrity, unalignment.Masalah yang dibahas dalam penelitian ini adalah keefektifan kalimat dalam laporan perjalanan siswa kelas VIII MTs Hidayatul Muslihin Kabupaten Way Kanan tahun pelajaran 2011/2012. Penelitian ini bertujuan untuk mendeskripsikan keefektifan kalimat yang meliputi keutuhan, kesejajaran, ketegasan, dan kehematan dalam laporan perjalanan siswa kelas VIII MTs Hidayatul Muslihin Kabupaten Way Kanan tahun pelajaran 2011/2012. Metode dalam penelitian ini adalah metode deskriptif kualitif. Sumber data penelitian ini adalah laporan perjalanan siswa kelas VIII MTs Hidayatul Muslihin kabupaten Way Kanan tahun pelajaran 2011/2012 berjumlah 30 laporan. Dari sumber data yang telah ditetapkan terdapat 515 kalimat. Berdasarkan hasil analisis, diketahui keefektifan kalimat 345 kalimat dengan persentase 66,99, sedangkan ketidakefektifan kalimat 170 kalimat dengan persentase 33,01. Ketidakefektifan kalimat tersebut meliputi ketidakutuhan, ketidaksejajaran, ketidakhematan.Kata kunci: kalimat, keefektifan, laporan perjalanan.